Measurement of Dosimetric Parameters and Dose Verification in Stereotactic Radiosurgery (SRS) - Reduan Abdullah; Nik Ruzman Nik Idris; Ahmad Zakaria; Ahmad Lutfi Yusof; Mazurawati Mohamed; Nur Iziana Mohsin (Penerbit UKM, 2015)
The first part of this study was about measurement of dosimetric parameters for small photon beams to be used as input data for treatment planning computer system (TPS) and to verify the dose calculated by TPS in Stereotactic Radiosurgery (SRS) procedure. The beam data required were percentage depth dose (PDD), off-axis ratio (OAR) and scattering factor. Small beams of 5 mm to 45 mm diameter from a circular cone collimator in SRS were used for beam data measurements. Measurements were made using pinpoint ionisation chamber (0.016cc). In the second part of this study, we reported the important of carrying out quality assurance (QA) procedures before SRS treatment which were found to infl uence the accuracy of dose delivery. These QA procedures consisted of measurements on the accuracy in target localization and treatment room laser alignment. The calculated TPS dose for treatment was verifi ed using pinpoint ionisation chamber and thermoluminescent detector (TLD) 100H. The deviation mean between measured and calculated dose was -3.28%. The measured dose obtained from pinpoint ionisation chamber is in good agreement with the calculated dose from TPS with deviation mean of 2.17%. In conclusion, pinpoint ionisation chamber gives a better accuracy in dose calculation compared to TLD 100H. The results are acceptable as recommended by International Commission on Radiation Units and Measurements (ICRU) Report No. 50 (1994) that dose delivered to the target volume must be within ± 5% error.